Anopheles salivary antigens as serological biomarkers of vector exposure and malaria transmission: A systematic review with multilevel modelling - Ellen A. Kearney (2022)
Background: Entomological surveillance for malaria is inherently resource-intensive and produces crude population-level measures of vector exposure which are insensitive in low-transmission settings. Antibodies against Anopheles salivary proteins measured at the individual-level may serve as proxy biomarkers for vector exposure and malaria transmission, but their relationship is yet to be quantified. Methods: A systematic review of studies measuring antibodies against Anopheles salivary antigens (PROSPERO: CRD42020185449). Multilevel modelling (to account for multiple study-specific observations (level-one), nested within study (level-two), and study nested within country (levelthree)) estimated associations between seroprevalence with Anopheles human biting rate (HBR) and malaria transmission measures. Results: From 3981 studies identified in literature searches, 42 studies across 16 countries were included contributing 393 study-specific observations of anti-Anopheles salivary antibodies determined in 42,764 samples. A positive association between HBR (log transformed) and seroprevalence was found; overall a 2-fold (100% relative) increase in HBR was associated with a 23% increase in odds of seropositivity (OR: 1.23, 95%CI: 1.10-1.37, p<0.001). The association between HBR and Anopheles salivary antibodies was strongest with concordant, rather than discordant Anopheles species. Seroprevalence was also significantly positively associated with established epidemiological measures of malaria transmission: entomological inoculation rate, Plasmodium spp. prevalence, and malarial endemicity class. Conclusions: Anopheles salivary antibody biomarkers can serve as a proxy measure for HBR and malaria transmission, and could monitor malaria receptivity of a population to sustain malaria transmission. Validation of Anopheles species-specific biomarkers are important given the global heterogeneity in the distribution of Anopheles species. Salivary biomarkers have the potential to transform surveillance by replacing impractical, inaccurate entomological investigations, especially in areas progressing towards malaria elimination.